2012
DOI: 10.1161/atvbaha.111.242388
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Isoform ε Negatively Regulates ADP-Induced Calcium Mobilization and Thromboxane Generation in Platelets

Abstract: Objective— Members of the protein kinase C (PKC) family are shown to positively and negatively regulate platelet activation. Although positive regulatory roles are extensively studied, negative regulatory roles of PKCs are poorly understood. We investigated the mechanism and specific isoforms involved in PKC-mediated negative regulation of ADP-induced functional responses. Methods and Results— A pan-PKC inhibitor, GF109203X, potentiated A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
48
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 53 publications
11
48
1
3
Order By: Relevance
“…In platelets from PKCε null mouse, Pears et al showed a marked inhibition of aggregation and dense granule secretion in response to GPVI agonists but no significant functional change in response to ADP [24]. At the opposite, recently Bynagari-Settipalli et al [26] showed an increase in ADP-induced aggregation and secretion in platelets from PKCε null mice. Indeed, signaling through GPVI suggests a role for PKCε in the initial steps of thrombus formation in mouse platelets.…”
Section: Introductionmentioning
confidence: 98%
“…In platelets from PKCε null mouse, Pears et al showed a marked inhibition of aggregation and dense granule secretion in response to GPVI agonists but no significant functional change in response to ADP [24]. At the opposite, recently Bynagari-Settipalli et al [26] showed an increase in ADP-induced aggregation and secretion in platelets from PKCε null mice. Indeed, signaling through GPVI suggests a role for PKCε in the initial steps of thrombus formation in mouse platelets.…”
Section: Introductionmentioning
confidence: 98%
“…S1). The level of PKCε in human platelets, however, is unclear as we were not able to detect expression using commercially available antibodies, although a recent study using an in‐house antibody has reported robust expression [8].…”
Section: Resultsmentioning
confidence: 91%
“…Robust expression of several isoforms has been reported in human (α, β, δ, θ) and mouse (α, β, ε, δ, θ) platelets, with evidence of expression of additional isoforms. In contrast, there are conflicting reports on expression of PKCε in human platelets [4–7], although a recent study using an in‐house antibody has demonstrated robust expression [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ oscillations, Ca 2+ sensitization, and contraction were shown to be activated by PKC in small airway smooth muscle . Conversely, PKC was shown to negatively regulate ADP‐induced Ca 2+ mobilization and thromboxane generation in platelets . Because 30% of TMP‐induced [Ca 2+ ] i rises was via Ca 2+ influx, this influx appears to be contributed by PKC‐regulated store‐operated Ca 2+ entry.…”
Section: Discussionmentioning
confidence: 99%